Intravital imaging of hemodynamic glomerular effects of enalapril or/and empagliflozin in STZ-diabetic mice - Kroeger, Hannah; Kessel, Friederike; Sradnick, Jan; Todorov, Vladimir; Gembardt, Florian; Hugo, Christian (Frontiers in Physiology, 2022)
Background Diabetic kidney disease is the leading cause of end-stage renal disease. Administration of ACE inhibitors or/and SGLT2 inhibitors show renoprotective effects in diabetic and other kidney diseases. The underlying renoprotective mechanisms of SGLT2 inhibition, especially in combination with ACE inhibition, are incompletely understood. We used longitudinal intravital microscopy to directly elucidate glomerular hemodynamics on a single nephron level in response to the ACE inhibitor enalapril or/and the SGLT2 inhibitor empagliflozin. Methods Five weeks after the induction of diabetes by streptozotocin, male C57BL/6 mice were treated with enalapril, empagliflozin, enalapril/empagliflozin or placebo for three days. To identify hemodynamic regulation mechanisms, longitudinal intravital multiphoton microscopy was employed to measure single nephron glomerular filtration rate (snGFR) and afferent/efferent arteriole width. Results Diabetic mice presented a significant hyperfiltration. Compared to placebo treatment, snGFR was reduced in response to enalapril, empagliflozin, or enalapril/empagliflozin administration under diabetic conditions. While enalapril treatment caused significant dilation of the efferent arteriole (12.55 ± 1.46 µm vs. control 11.92 ± 1.04 µm, p<0.05), empagliflozin led to a decreased afferent arteriole diameter (11.19 ± 2.55 µm vs. control 12.35 ± 1.32 µm, p<0.05) in diabetic mice. Unexpectedly under diabetic conditions, the combined treatment with enalapril/empagliflozin had no effects on both afferent and efferent arteriole diameter change. Conclusion SGLT2 inhibition, besides ACE inhibition, is an essential hemodynamic regulator of glomerular filtration during diabetes mellitus. Nevertheless, additional mechanisms – independent from hemodynamic regulation - are involved in the nephroprotective effects especially of the combination therapy and should be further explored in future studies.